The Effectiveness of Inclusive Education Practices on Social Outcomes for Students with Disabilities - Labra, Janice; Pinili, Lilibeth; Saladaga, Lindley; Calasang, Veronica (International Journal of Social Sciences and English Literature, 2025)
This study assessed the relationship between inclusive education practices and the social outcomes of students, including sense of belonging, collaboration skills, and conflict resolution. Inclusive education practices assessed include teaching strategies, classroom modifications, and support services. Data from students were analyzed to determine the significance of these practices in influencing social outcomes. The findings revealed no significant relationship between the level of inclusive education practices and the measured social outcomes. Teaching strategies, classroom modifications, and support services showed weak or negligible correlations with students’ sense of belonging, collaboration skills, and conflict resolution. Despite these results, the study highlights the critical role of inclusive education in promoting accessibility and participation for all students. The lack of measurable impact on social outcomes suggests that factors beyond the assessed practices, such as peer interactions, family influence, or school culture, may play a more prominent role in shaping social skills. Based on these findings, the study recommends targeted interventions, such as social skills training, fostering supportive school cultures, integrating social-emotional learning (SEL), and enhancing teacher training in managing social dynamics. These strategies aim to bridge the gap between inclusive education practices and social development. The study emphasizes the need for holistic approaches that combine academic support with intentional efforts to nurture students’ interpersonal growth, ensuring both academic success and social well-being in inclusive educational settings.